Explaining the Quality of Teacher and Student Communication Based on Cooperation Principles in a Religious Context: A Pragmatic Study - Meisya Novitasari; Lilik Wahyuni (Universitas Pendidikan Mandalika, 2024)
Communication in the classroom has a very important role because there is a process by which a teacher transfers knowledge and other aspects of education to students. If the principle of cooperation is violated, then the communication will be counterproductive and not in accordance with its initial purpose. This research aims to obtain an objective picture of the quality of communication based on the fulfillment and deviation of the principle of cooperation in teacher and student communication in a religious context at Shalahuddin Middle School. This research is descriptive research using a qualitative approach. The data collection techniques used were observation and note taking. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this research are that there is a fulfillment of the principles of cooperation in the form of the maxim of quantity, the maxim of quality, the maxim of method, and the maxim of relevance, as well as deviations from the principles of cooperation in the form of the maxim of quantity, the maxim of quality, the maxim of method, and the maxim of relevance in the religious context at Shalahuddin Middle School.